2023
DOI: 10.1038/s41467-023-35797-6
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel proteomic analyses reveal molecular diversity between diffuse-type and intestinal-type gastric cancer

Abstract: Diffuse-type gastric cancer (DGC) and intestinal-type gastric cancer (IGC) are the major histological types of gastric cancer (GC). The molecular mechanism underlying DGC and IGC differences are poorly understood. In this research, we carry out multilevel proteomic analyses, including proteome, phospho-proteome, and transcription factor (TF) activity profiles, of 196 cases covering DGC and IGC in Chinese patients. Integrative proteogenomic analysis reveals ARIDIA mutation associated with opposite prognostic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Also, when analyzing elderly patients, women had higher risk of death compared to elderly man. Our findings are in agreement with several publications, where female patients have worse OS than males, regardless of age, due to the greater presence of poor prognostic factors such as histology and clinical stage as mentioned before ( 4 , 21 , 30 , 36 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Also, when analyzing elderly patients, women had higher risk of death compared to elderly man. Our findings are in agreement with several publications, where female patients have worse OS than males, regardless of age, due to the greater presence of poor prognostic factors such as histology and clinical stage as mentioned before ( 4 , 21 , 30 , 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…The incidence of young age at the time of diagnosis has increased over the past decade, defined as “early onset of GC”, these populations have demonstrated to highlight the prevalence of these 3 features of bad prognosis, besides higher metastatic risk ( 19 , 21 , 30 ). Besides, the early onset of gastric cancer has also been associated with hereditary diffuse gastric cancer, which is an autosomal dominant cancer syndrome caused by the inactivation of germline mutations in E-cadherin, tumor suppressor gene (CDH1), and less frequently variants in CTNNA1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that NK cells and T cells secrete a variety of pro‐inflammatory factors that exert a tumor‐killing effect 28,29 . Conversely, Th2 cells can produce pro‐tumor progression factors, and their abundance has been linked to malignant progression in several cancer types, including LUAD, gastric cancer and colorectal cancer 30–32 . Consequently, our findings suggest that JAM2 may function as a tumor suppressor and significantly modulate LUAD progression.…”
Section: Discussionmentioning
confidence: 61%
“…[25][26][27] Tumor progression is not solely driven by genetic mutations within to malignant progression in several cancer types, including LUAD, gastric cancer and colorectal cancer. [30][31][32] Consequently, our findings suggest that JAM2 may function as a tumor suppressor and significantly modulate LUAD progression.…”
Section: Discussionmentioning
confidence: 71%
“…The validation cohort (https://www.iprox.cn//page/subproject. html?id=IPX0004819001) is a group of GC patients treated with anti-PD1 therapy, including seven responder cases and seven nonresponder cases (Shi et al, 2023). The sample is also FFPE, and the proteins were quantified using an MS-based label-free method.…”
Section: Validation Data Processingmentioning
confidence: 99%